An imaging investigation of in situ uroliths in hospitalized cats in New Zealand and in the United States. Issue 4 (6th July 2016) - Wightman, Paul F.; Hill, Kate E.; Cohen, Eli B.; Bridges, Janis; Bolwell, Charlotte F.; French, John; Adler, Brian A.; Green, Ron
Abstract: The submission rates of feline uroliths to laboratories and the composition of uroliths have been reported in studies. The prevalence of uroliths reported on imaging findings has not been published. The objective of this retrospective study was to use imaging data to investigate the anatomical location and the prevalence of macroscopic in situ uroliths in cats. Radiographs, sonograms and imaging reports from two cohorts of cats (from New Zealand ( n  = 497) and the United States ( n  = 693)) from 2004‐2013 were reviewed for the presence of in situ uroliths. Uroliths were categorized by their location in the lower or upper urinary tract. Radiographic studies were performed on 43% (212/497) of the cats from New Zealand and 50% (349/693) of the cats from the USA. Sonographic studies were performed on 57% (285/497) of the cats from New Zealand and 50% (344/693) of the cats from the USA. The total prevalence of uroliths was 3% in the New Zealand cohort and 13% in the USA cohort. Lower tract urolith prevalence in the New Zealand cohort was 2.4% (5/212) in cats ≤ 6y and 1.1% (3/285) in cats >6y. Upper tract urolith prevalence in the New Zealand cohort was 0.5% (1/212) in cats ≤ 6y and 1.8% (5/285) in cats >6y. Lower tract urolith prevalence in the United States cohort was 6.0% (11/183) in cats ≤ 6y and 2.9% (15/510) in cats >6y. Upper tract urolith prevalence in the United States cohort was 2.7% (5/183) in cats ≤ 6y and 10.2% (52/510) in cats >6y. The prevalence of uroliths in the upper tract or lower tract was low in the New Zealand cohort compared to that of cats in the USA cohort, irrespective of age category. Geographical location may be important when evaluating risk factors for feline urolithiasis. Abstract : The prevalence of uroliths in the upper tract or lower tract was low in the New Zealand cats presented for abdominal imaging compared with that of cats in the USA cohort, irrespective of age category. Geographical location may be an important when evaluating risk factors for feline urolithiasis